2022
DOI: 10.1149/1945-7111/ac97c6
|View full text |Cite|
|
Sign up to set email alerts
|

A Solid/Liquid High-Energy-Density Storage Concept for Redox Flow Batteries and Its Demonstration in an H2-V System

Abstract: Redox flow batteries (RFBs) are ideal for large-scale, long-term energy storage applications. However, the limited solubility of most ions and compounds in aqueous and non-aqueous solvents (1-1.5 M) restricts its use in the days-energy storage scenario, which necessitates a huge volume of solution in the numerous tanks and the vast floorspace for these tanks, making an RFB systems costly. To resolve the low energy storage density issue, this work presents a novel way in which the reactants and products are sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The reference exchange current density (j0ref) and the catalyst loading density (mPt) used in the CL are unlikely to be affected by the hydrophobic treatment. Furthermore, our in‐situ ECSA measurement reveals that the hydrophobic treatment has minimal influence on the cathode's ECSA (aPt in Equation ()) 10 . Therefore, Equation () shows that the only possible reason for the fuel cell improvement in the kinetic‐controlled region is related to the oxygen concentration in the ionomer near the catalyst surface (CnormalO), which is supposed to be determined by the oxygen solubility in the Nafion ionomer phase.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The reference exchange current density (j0ref) and the catalyst loading density (mPt) used in the CL are unlikely to be affected by the hydrophobic treatment. Furthermore, our in‐situ ECSA measurement reveals that the hydrophobic treatment has minimal influence on the cathode's ECSA (aPt in Equation ()) 10 . Therefore, Equation () shows that the only possible reason for the fuel cell improvement in the kinetic‐controlled region is related to the oxygen concentration in the ionomer near the catalyst surface (CnormalO), which is supposed to be determined by the oxygen solubility in the Nafion ionomer phase.…”
Section: Resultsmentioning
confidence: 89%
“…It provides more efficient pathways for the oxygen transport for the dissolved oxygen from the ionomer/air interface to the ionomer/catalyst interface. A more detailed explanation of the oxygen transport phenomenon along this direction is given in reference 10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Our previous research identified a type of pseudostable, precipitated VOSO 4 (V 4+ ) solid with a more amorphous, low-crystalline, gel-like structure. 14 This gel-like solid exhibits a high dissolution rate. Since it is easier to reconvert the solid electrolyte into its liquid form when sulfate anions remain dissociated from vanadium cations, it is necessary to maintain additional water molecules in the secondary solvation shell.…”
Section: Introductionmentioning
confidence: 99%